Predicting the biological activity of selected phytochemicals in Alsophila spinulosa leaves against 4-aminobutyrate-aminotransferase: A potential antiepilepsy agents - Kolawole, Oyebamiji Abel; Eniola, Olujinmi Faith; Adewale, Akintelu Sunday; Babatunde, Adetuyi; Olubanke, Ogunlana; Banjo, Semire; Temitope, Akintayo Emmanuel; Olufunke, Akintayo Cecilia; Oyebamiji, Babalola Jonathan; Mary, Olawoye Bolanle; Oluwasayo, Aworinde Juliana (Eclética Química, 2024)
The use of medicinal plants as an alternative mean of treating various diseases has drawn the attention of several researchers. The desire to find lasting solutions to epilepsy among humans increases every day. Thus, this work was aimed at investigating the potential capacity of the studied phytochemicals in Alsophila spinulosa against human 4-aminobutyrate-aminotransferase as well as to predict the nonbonding interactions involved in the studied complexes. In this work, ten compounds with biological activities were selected and studied using molecular docking method. The molecules selected obtained from A. spinulosa leaves were optimized and various descriptors that described the anti-4-aminobutyrate-aminotransferase features were obtained. More so, 2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-3-(((2S,3R,4R,5R,6S)-3,4,5-trihydroxy-6-methyltetrahydro-2H-pyran-2-yl)oxy)-4H-chromen-4-one (compound 9) with highest binding affinity proved to have greater strength to inhibit 4-aminobutyrate-aminotransferase thereby downregulating epilepsy than other studied compounds and the reference drug (clobazam). The ADMET features of both compound 9 and clobazam were explored and reported.